Certain psychological factors influencing artistic thinking in perception of poetry - Dzikarienė , V. (Psichologija, 1971)
Perception and interpretation of poetry requires active artistic thinking on the reader's part. The main thing is not resorting to knowledge but imagination and experience processes. The formation of an adequate poetical image is mostly dependent on directed imaginative and emotional dynamics of those being tested. The dynamics of these psychical processes is guided both by the sensation of emotional tone of poetry and by that of essential image.
Keywords: artistic thinking; perception of poetry